Gastrodia isabelensis and G. solomonensis (Gastrodieae, Epidendroideae, Orchidaceae): two new species representing a new generic record in the Solomon Islands - Hsu, Tian-Chuan; Fanerii, Moffat; Yang, Tsung-Yu Aleck; Pitisopa, Fred; Li, Chia-Wei (Phytotaxa, 2016)
Two new mycoheterotrophic orchids, Gastrodia isabelensis and G. solomonensis, are described and illustrated from the Solomon Islands. The genus Gastrodia is also recorded in the country for the first time. Gastrodia isabelensis is close to G. callosa from Java and Taiwan but differs in having longer inflorescences, broadly ovate to semiorbicular sepal lobes, ovate-orbicular petal lobes and lips with mauve basal calli, semiorbicular epichiles and greenish brown apical keels. Gastrodia solomonensis is close to G. queenslandica from NE Australia but is distinguished by having much longer perianth tubes, larger lips with elliptic mesochiles, and wider columns.